OGBN P12 Minimising the systemic effects of an oesophageal leak following high risk myotomy repair using Prophylactic Endoluminal Vacuum Therapy (EVT) - time for a change?. (7th December 2022) - Noorani, Ayesha; Tham, Ji Chung; Bennett, John; Gourgiotis, Stavros; Hardwick, Richard; Sujendran, Vijay; Safranek, Peter; Hindmarsh, Andrew
Abstract: Background: Endoluminal Vacuum Therapy (EVT) continues to gain momentum as a first line treatment for oesophageal perforations. Outside the emergency setting there is growing interest in using EVT prophylactically to protect high-risk elective oesophageal repairs. We present a case which demonstrates the benefit of prophylactic EVT in preventing extraluminal contamination, mediastinitis and sepsis following elective oesophageal surgery. Methods: An 80-year-old female underwent laparoscopic Hellers Myotomy and Dor Fundoplication for Type 2 Achalasia following worsening symptoms including weight loss despite nutritional optimisation. She had multiple prior balloon dilatations without long term symptom control and remained frail, with a performance status of 0 and an ASA 2. During surgery the oesophageal myotomy was challenging due to extensive scarring. Endoscopy was performed on completion of the myotomy to confirm adequacy and a 1cm oesophageal perforation at 38cm was noted. Primary repair was performed with 5 interrupted 3/0 maxon sutures. An ad-hoc EVT device was constructed using V.A.C granufoam (KCI) sutured to the end of an 18Fr nasogastric tube, and placed intraluminally in the oesophagus across the repair. Continuous negative pressure of 75mmHg was applied. Post operatively the patient was kept nil by mouth and received parenteral nutrition. Her clinical and biochemical parameters were monitored, and the progress of her oesophageal repair was assessed endoscopically. Results: The first post-operative endoscopy was performed at day 4. On visual inspection a full thickness oesophageal defect was seen at the proximal aspect of the oesophageal repair. There was no associated leak cavity or other endoscopic evidence of extraluminal contamination. A further ad-hoc EVT device was constructed and placed intraluminally in the oesophagus across the suture repair and oesophageal wall defect. A second endoscopy was performed on day 10 post-operative and the oesophageal defect had completely healed. Despite having a documented full thickness oesophageal wall defect the patient remained clinically well throughout her post-operative recovery with no clinical signs of sepsis. The highest recorded CRP was 131 and WCC was 12.7 on day 1 and day 8 respectively. At no point was a higher level of care or input required than the general surgical ward. Her total LOS was 14 days. Conclusions: A leak following elective oesophageal surgery is a serious complication which may result in mediastinitis, sepsis and death. This case demonstrates the utility of prophylactic EVT in reducing the impact of an oesophageal leak in patients where breakdown of the oesophageal repair occurs. Without prophylactic EVT in this case, we are certain the breakdown of the oesophageal repair would have resulted in a significant oesophageal leak with mediastinitis and sepsis which an 80-year-old patient with limited physiological reserve may not have survived. While prophylactic EVT is not a substitute for sound surgical technique, it should be considered in high-risk patients undergoing elective oesophageal surgery to reduce or prevent the septic hit consequent to an oesophageal leak if breakdown of an oesophageal repair occurs.